The Interaction Between Self-Efficacy, Fear of Failure, and Entrepreneurial Passion: Evidence from Business Students in Emerging Economies - Elizabeth Emperatriz García-Salirrosas; Dany Yudet Millones-Liza; Rafael Fernando Rondon-Eusebio; Jorge Alberto Esponda-Pérez; Eulalia Elizabeth Salas-Tenesaca; Reinaldo Armas-Herrera; María Fernanda Zumba-Zúñiga (Behavioral Sciences, 2025)
This study examines the relationship between fear of failure, entrepreneurial passion, and entrepreneurial self-efficacy among university business students from four emerging Latin American economies: Mexico, Colombia, Peru, and Ecuador. This research addresses the need to understand the psychological factors that influence entrepreneurship, particularly in developing economies. Using non-probability convenience sampling, surveys were distributed between June 2021 and August 2022, and 961 valid responses were obtained. Scales from renowned researchers were used, which were translated and semantically validated in Spanish to measure the three variables. The data were analyzed using structural equation modeling with PLS. The overall results reveal that fear of failure negatively affects entrepreneurial passion, while entrepreneurial passion has a positive and significant relationship with entrepreneurial self-efficacy. Furthermore, entrepreneurial passion has a positive and significant relationship with fear of failure and entrepreneurial self-efficacy, with substantial differences between countries. Gender differences were also identified: in women, all relationships in the model were significant, while in men, the direct effect of fear of failure on entrepreneurial self-efficacy did not reach statistical significance. These findings contribute to the entrepreneurship literature by demonstrating that the relationship between these psychological variables varies by context (country) and gender, contradicting the notion of a universal effect.